Optimizing Order Fulfillment through Advanced ERP Systems: A Case Study on Oracle NetSuite - Tulli, Sai krishna Chaitanya (International Journal of Scientific Research and Management (IJSRM), 2023)
Order fulfillment is a critical aspect of supply chain management that significantly impacts customer satisfaction, operational efficiency, and profitability. This study explores the role of advanced Enterprise Resource Planning (ERP) systems in optimizing order fulfillment, with a focus on Oracle NetSuite as a case study. By leveraging its robust capabilities, including real-time tracking, automation, and integration of supply chain processes, Oracle NetSuite addresses common challenges such as inventory inaccuracies, delayed shipments, and inefficient workflows. The research employs both qualitative and quantitative methodologies to evaluate the system’s impact on key performance indicators (KPIs) such as order accuracy, lead time, and customer satisfaction. Findings reveal substantial improvements in operational efficiency and order processing times, demonstrating Oracle NetSuite’s value in modernizing supply chain operations. The study concludes with practical recommendations for implementation and continuous optimization strategies, underscoring the importance of adopting advanced ERP solutions for sustainable competitive advantage in dynamic business environments.